Against epistemological virus of scepticism : Davidson on objectivity of knowledge - Šljivo, Kenan (Array, 2020)
This paper provides a short overview of approaches to epistemological issues as represented by Donald Davidson, an American philosopher. This is an attempt to analyse Davidson’s essential postulates, in order to construct a framework for understanding a highly authentic epistemological position and the way in which it appears as an antipode to the sceptical epistemological strategies. In other words – the goal is to identify a coordinate system, through a set of postulates, from which Davidson projects his epistemological attitudes. For that purpose, the paper presents the developmental process of Davidson’s epistemological thought that goes through triangulation of notions subjective, intersubjective, and objective. The paper places special emphasis on Davidson’s concentration on communicative practices and intersubjectivity as the only topoi in which the issue of objectivity can be raised.